Structural Evaluation of Conventional and Modified Flexible Pavement Performance - Mensahn, E. S. K.; Wada, S. A.; Lugeiyamu, L. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Experimental studies indicate that using rubber particles (RP) as additives improves hot mix asphalt (HMA) engineering properties when used as a road surface layer. Two critical strains are identified with asphalt pavement: horizontal tensile strain beneath the AC layer and vertical compressive strain on top of the subgrade. However, these strains are difficult to be predicted by experimental simulations. This research aims to conduct a comparative structural performance evaluation of conventional and modified asphalt pavement cross-sections with a particular reference to compute pavement responses (stress, strain, deflection, and stiffness) by utilizing Kenlayer computer code. Each cross-section is modelled as an elastic multilayer system consisting of five (5) layers with assigned material properties. The pavement compositions illustrate a typical highway pavement structure. The elastic modulus for both HMA materials was obtained at the average design temperature of 25˚C to reflect tropical and subtropical regions. The standard tandem axle load that causes damage to the pavement having a contact pressure of 673 kPa (0.673 MPa) with a set of dual tires center to center spacing of 33.75 cm was considered. The similarities and differences between the two pavement cross-sections concerning performance responses are compared. The analysis revealed that for both conventional and modified HMA cross-sections, the horizontal tensile strains at the bottom of the surface and binder layers are (2.62E-06 & -172E-04) and (-2.04E-05 & -2.14E-04) µε; at the same time, the vertical compressive strains on top of the subgrade are (1.57E-04) and (1.69E-04) µε. And finally, the computed surface layer stiffnesses are (833.51 kN/cm) and (734.89 kN/cm). It is appropriate to say that the modified HMA significantly decreases the surface layer’s stiffness; as such, it eventually prolongs the rapid encroachment of fatigue cracking and rutting deformation.